Electrooxidation study of methanol using H2O2 and air as mixed oxidant at cathode in air breathing microfluidic fuel cell - Rathoure A.K.; Pramanik H. (My University, 2025)
The electrooxidation study of methanol was performed at room temperature of 34 °C in a membraneless air breathing microfluidic fuel cell using laboratory made carbon cloth/gas diffusion layer (GDL). The anode and cathode electrocatalysts were Pt[sbnd]Ru (30%:15% by wt.)/High Surface Area Carbon (CHSA) (Alfa Aesar, USA) and Pt (40% by wt.)/CHSA(Alfa Aesar, USA) respectively. The electrocatalyst loading at anode and cathode were similar, in the order of 1 mg/cm2. The oxidants at cathode were atmospheric oxygen or H2O2combined with atmospheric oxygen (air). The cell voltage and current density were measured for different concentration of fuel (methanol), oxidant (H2O2) and electrolyte (KOH), respectively. The maximum open circuit voltage (OCV) of 0.47 V and power density of 0.97 mW/cm2at a current density of 6.9 mA/cm2were obtained for the fuel of 0.5 M methanol mixed with 1 M KOH and atmospheric fresh air as oxidant with 1 M KOH at cathode. Whereas, the maximum OCV of 0.68 V and power density of 3.8 mW/cm2at a current density of 18.75 mA/cm2were for methanol as fuel of 1 M mixed with 1 M KOH as electrolyte and 2 M H2O2as oxidant at cathode mixed with 1 M KOH as electrolyte in the presence of continuous diffusion of atmospheric fresh air. © 2016 Hydrogen Energy Publications LLC